Constraints Faced and Suggestions Provided During the Use of Advanced Communication Media by Extension Personnel of State Department of Agriculture in Nagpur District - Pravin N. Chavhan , V. S. Tekale , and M. K. Rathod, (Indian Journal of Extension Education, 2017)
During the study conducted at Nagpur District of Maharashtra, the major constraints found during the use of advancedcommunication media were literacy level of end user (92.00 %), training (82.00 %), accessibility and networking (80.00%). Over these constraints some suggestions that are given for improvement are proper training, immediate feedback,providing network connectivity and IT for rural areas etc. The respondents were suggested for providing networkconnectivity in rural areas (93.00 %) in addition with that appropriate training to extension personnel related to advancedcommunication media (83.00 %) and telecom and ITservices for rural areas should also be provided.